Porous aluminum lithium LDH for lithium ion adsorption and preparation method thereof
By loading titanium oxide doped aluminum lithium LDH on porous PVC, the adsorption capacity and specific surface area of lithium ions are improved, and the problem of low adsorption capacity in the prior art is solved, and efficient lithium ion adsorption and recycling are achieved.
Patent Information
- Application Number
- CN202411536505.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
AI Technical Summary
The existing aluminum lithium LDH has a low adsorption capacity and is difficult to meet the needs of lithium ion enrichment and recovery.
By loading the highly diffuse titanium oxide doped aluminum lithium LDH on porous PVC, the adsorption and desorption path of lithium ions is shortened, the adsorption amount is increased, and the preparation process is optimized to increase the specific surface area through the use of eutectic solvents and DMF. and adsorption capacity.
The specific surface area is achieved to reach 198.57~205.58m2/g, the adsorption capacity is 19~22mg/g, and the adsorbed material can be eluted with hot water, which has good recycling performance and reduces the separation cost of lithium ions.
Smart Images

Figure CN119281305A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion enrichment and recovery, and more specifically to a porous aluminum lithium LDH for lithium ion adsorption and a preparation method thereof. Background Art
[0002] Lithium is an important strategic energy metal, mainly used in the manufacture of lithium-ion batteries. It is known as the metal that drives the world forward. In recent years, the lithium battery industry has developed rapidly. By 2050, the global demand for lithium is expected to reach 11.2 million tons. The sources of lithium resources mainly include secondary resources such as lithium ore, salt lake brine and waste lithium batteries, and lithium ions are initially enriched in the solution. Adsorption is one of the main methods for extracting lithium ions from solution, which requires the use of adsorption materials. Among adsorption materials, aluminum salt adsorbent is the most widely used and highly researched adsorbent, with the advantage of low cost. However, aluminum salt adsorbent has the disadvantage of low adsorption capacity.
[0003] In the field of aluminum salt adsorbents, the most extensive research is on the adsorption capacity of aluminum-lithium LDH. How to improve the adsorption capacity of aluminum-lithium LDH has always been a research hotspot in the field of lithium ion enrichment and recovery. For example, patent CN110639467A discloses a method for preparing a magnetic aluminum salt lithium adsorbent, which uses magnetic recovery to solve the separation problem of solid powder and solution. However, due to the addition of magnetic substances, the adsorption capacity is further reduced, and the adsorption capacity is only 5.90 mg / g; patent CN109078602A discloses a magnetic microporous lithium adsorbent and a preparation method thereof, which also uses magnetic recovery to solve the separation problem of solid powder and solution. Organic solvents are added during the preparation process, and the adsorption capacity is increased to 9.5-14.3 mg / g; patent CN117816126A discloses a method for preparing an aluminum-based lithium adsorbent based on DFT screening and its application, which prepares carbonate-intercalated aluminum-lithium LDH, and the adsorption capacity reaches 18.3 mg·g -1 .
[0004] For example, the coprecipitation method was used to prepare a 161 m 2 / g of Li / Al-LDHs, the adsorption capacity is 7.27mg / g; the specific surface area of LDHs-A synthesized in the literature Zhou H, Li J, Xu L, et al, Materials Letters, 2023, 340: 134159 is 58.30m 2 / g, for Li + The adsorption capacity is 6.69 mg / g.
[0005] However, the adsorption capacity of aluminum-lithium LDH in the above existing studies is still relatively low. Therefore, it is of great significance to further improve the adsorption capacity of aluminum-lithium LDH. Summary of the invention
[0006] One of the purposes of the present invention is to provide a porous aluminum-lithium LDH for lithium ion adsorption, thereby solving the technical problem that the existing aluminum-lithium LDH has a low lithium ion adsorption capacity. The aluminum-lithium LDH of the present invention has a higher adsorption capacity for lithium ions.
[0007] Another object of the present invention is to provide a method for preparing the above-mentioned porous aluminum-lithium LDH. During the preparation of aluminum-lithium LDH, a highly dispersed LDH precursor is loaded on PVC, thereby increasing the specific surface area of the aluminum-lithium LDH, thereby preparing an aluminum-lithium LDH with a high adsorption amount.
[0008] In order to achieve the above object, the technical solution provided by the present invention is:
[0009] The first aspect of the present invention provides a porous aluminum-lithium LDH for lithium ion adsorption, comprising porous PVC and titanium oxide-doped aluminum-lithium LDH (TiO2@AlLi-LDH), wherein the porous PVC is used as a carrier, and the titanium oxide-doped aluminum-lithium LDH layer is dispersedly loaded on the PVC; its XRD spectrum shows that the LDH characteristic peaks at 20.62°, 23.68°, 63.22° and 64.53° are significantly broadened to a bulging state.
[0010] The porous aluminum-lithium LDH of the present invention comprises porous PVC and TiO2@AlLi-LDH, wherein PVC is a porous structure and serves as a carrier of TiO2@AlLi-LDH. The Li-O(H)-Al layer in the TiO2@AlLi-LDH structure is combined with a polymer chain in PVC in a non-covalent interaction manner, thereby shortening the adsorption and desorption path of lithium ions. This is beneficial to increasing the adsorption amount of lithium ions and solving the technical problem of the difficulty in separating a powdered aluminum salt adsorbent from a solution. On the other hand, it is convenient for subsequent lithium ion elution treatment. The aluminum-lithium LDH after adsorption can use hot water to elute lithium ions, can be repeatedly adsorbed and has good recycling performance, thereby reducing the separation cost of lithium. In addition, the porous material of the aluminum-lithium LDH can be directly applied to industrial production.
[0011] Compared with the titanium oxide doped aluminum lithium LDH (TiO2@AlLi-LDH), the XRD spectrum of the porous aluminum lithium LDH (TiO2@PVC@AlLi-LDH) in the present invention further broadens the crystal characteristic peaks, and the characteristic peaks merge into a broad peak state, which further proves that the crystallization state of titanium oxide doped aluminum lithium LDH can be improved by loading treatment, and TiO2@AlLi-LDH is highly dispersed on the porous PVC carrier. In addition, compared with PVC@Pore, the characteristic peak positions in the infrared spectrum of TiO2@PVC@AlLi-LDH are basically the same, but some characteristic peaks change, especially in the fingerprint area 613 and 690cm -1 The characteristic peaks near the surface of the nanostructured carbon disappeared, indicating that after the addition of aluminum-lithium LDH powder, there was an interaction between polyvinyl chloride and aluminum-lithium LDH or TiO2.
[0012] Furthermore, the specific surface area of the porous aluminum-lithium LDH is 198.57-205.58 m 2 / g; and / or the adsorption capacity of the porous aluminum lithium LDH is 19 to 22 mg·g -1 .
[0013] The second aspect of the present invention provides a method for preparing a porous aluminum-lithium LDH for lithium ion adsorption, comprising: contacting or mixing aluminum ions, lithium ions and titanium ions in an alkaline aqueous solution to produce a coprecipitation reaction to form an aqueous suspension; adding a low eutectic solvent to the aqueous suspension and evaporating and removing water to form a highly dispersed aluminum-lithium LDH precursor mixed solution; adding a mixed solution of PVC and DMF to the aluminum-lithium LDH precursor mixed solution to form an organic phase suspension; and dripping the organic phase suspension into the aqueous phase to prepare the porous aluminum-lithium LDH.
[0014] In the process of preparing aluminum-lithium LDH, the present invention loads a highly dispersed LDH precursor on porous PVC; at the same time, compared with titanium oxide-doped aluminum-lithium LDH, the specific surface area of the porous aluminum-lithium LDH can be further increased.
[0015] Further preferably, a low eutectic solvent is added to the alkaline aqueous solution in which aluminum ions, lithium ions, and titanium ions undergo a coprecipitation reaction. The low eutectic solvent can act as a dispersant, preventing the suspension from precipitating or agglomerating, and improving the stability of the suspension; at the same time, in the process of evaporation and dehydration, it is beneficial to prevent the aluminum lithium LDH from crystallizing and not completely removing water in this process, thereby obtaining a highly dispersed aluminum lithium LDH precursor mixed solution. In addition, the low eutectic solvent in the highly dispersed aluminum lithium LDH precursor can also act as a complexing agent to achieve a complex connection between the LDH precursor and PVC.
[0016] More preferably, a mixed solution of PVC and DMF is added to a highly dispersed aluminum-lithium LDH precursor mixed solution, and the intermediate state of the aluminum-lithium LDH preparation process, i.e., the highly dispersed aluminum-lithium LDH precursor mixed solution, is loaded with PVC, which is different from mechanical solid-state granulation loading.
[0017] Finally, the organic phase suspension is dropped into the aqueous phase to form a mixed co-precipitation to obtain the porous aluminum lithium LDH.
[0018] Furthermore, the low eutectic solvent is a combination of choline chloride and urea, or a combination of DBU and MTU, or a combination of other low eutectic solvents containing a hydroxyl structure.
[0019] Furthermore, the aqueous suspension is evaporated to remove water, specifically, heated to a temperature of 80-120° C. for a duration of 24-48 hours.
[0020] Furthermore, the mass ratio of PVC to DMF is 1:(8-12), and the mixed solution is added dropwise into the highly dispersed aluminum-lithium LDH precursor mixed solution.
[0021] Furthermore, aluminum ions, lithium ions and titanium ions are contacted or mixed in an alkaline aqueous solution, specifically including: adding titanium tetrachloride to a lithium salt solution to obtain a titanium-containing lithium salt solution; and / or mixing a sodium aluminate solution with a titanium-containing lithium salt solution.
[0022] Furthermore, the concentration of aluminum ions in the sodium aluminate droplets is 80-150 g / L, wherein the ratio of the molar number of aluminum ions to the molar number of hydroxide ions is 2:(7-10).
[0023] Furthermore, the sodium aluminate solution is mixed with the titanium-containing lithium salt solution, specifically, the sodium aluminate solution is added dropwise to the titanium-containing lithium chloride solution using a constant flow pump, and the mixing temperature is 25-60° C.; the ratio of the molar number of lithium to the molar number of aluminum in the aqueous suspension is (1-2):2, and the molar ratio of titanium to aluminum is 1:(3-5).
[0024] Furthermore, the aqueous phase is an alcohol-containing aqueous solution, and the alcohol-containing aqueous solution includes ethanol or methanol in a volume fraction of 10 to 50%.
[0025] In summary, the technical solution provided by the present invention can achieve the following beneficial effects compared with the prior art:
[0026] (1) The porous aluminum-lithium LDH of the present invention is loaded with PVC by oxidation-doped aluminum-lithium LDH, and its crystal state is improved; compared with porous PVC (PVC@Pore), some characteristic peaks in its infrared spectrum have changed. Moreover, its surface area is 198.57-205.58 m 2 / g, when adsorbing lithium-containing solutions, its adsorption capacity can reach 19-22 mg g -1 The adsorbed aluminum-lithium LDH can be eluted with hot water to remove lithium ions, and can be repeatedly adsorbed and has good recycling performance, thereby reducing the separation cost of lithium.
[0027] (2) The preparation method of the present invention sequentially adds a low eutectic solvent to an alkaline aqueous solution of a mixture of aluminum ions, lithium ions, and titanium ions to achieve evaporation and dehydration to prepare a highly dispersed aluminum-lithium LDH precursor. In the above process, the low eutectic solvent acts as a dispersant and is also helpful in preventing the crystallization of aluminum-lithium LDH. After the subsequent addition of PVC, it can promote the complexation of the LDH precursor with PVC, and load the highly dispersed aluminum-lithium LDH intermediate state onto the dissolved PVC. This loading method is better than mechanical granulation loading. In addition, it is added dropwise to an alcohol-containing aqueous solution for granulation, thereby obtaining a spherical porous doped aluminum-lithium LDH layer plate loaded on PVC. This preparation method further increases the specific surface area of the porous aluminum-lithium LDH and improves the crystallization state of the porous aluminum-lithium LDH, thereby increasing its adsorption capacity for lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a process flow chart of the method for preparing porous aluminum-lithium LDH in Example 1 of the present invention.
[0029] Figure 2 This is the XRD diagram of the porous aluminum-lithium LDH prepared in Example 1 of the present invention before and after adsorption.
[0030] Figure 3 This is the infrared spectrum of the porous aluminum-lithium LDH prepared in Example 1 of the present invention.
[0031] Figure 4 This is a microscopic morphology of the aqueous suspension during the preparation process of Example 1 of the present invention.
[0032] Figure 5 This is a scanning electron microscope image of the porous aluminum-lithium LDH prepared in Example 1 of the present invention before and after adsorption.
[0033] Figure 6 This is a transmission electron microscope image of the porous aluminum-lithium LDH prepared in Example 1 of the present invention before adsorption. DETAILED DESCRIPTION
[0034] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with the accompanying drawings and embodiments.
[0035] In the following examples and comparative examples, when verifying the adsorption performance of the prepared aluminum lithium LDH on lithium-containing solutions, the lithium-containing solutions were all used for lithium hydroxide solutions. When adsorbing other lithium salt solutions with low hydroxide ion content such as lithium chloride and lithium sulfate, the pH of the lithium salt solution was adjusted with ammonia water or sodium hydroxide solution before adsorption. Specifically, the ratio of hydroxide ions to lithium ions in the adjusted lithium salt solution was greater than 1:1.
[0036] The deep eutectic solvents used in the following examples and comparative examples are a combination of choline chloride and urea, or a combination of DBU and MTU. It should be understood that other combinations of deep eutectic solvents containing hydroxyl structures are also possible.
[0037] Example 1
[0038] The preparation process of this embodiment is as follows Figure 1 As shown, specifically including:
[0039] (1) Aluminum hydroxide and sodium hydroxide are used as raw materials to prepare a sodium aluminate solution. The aluminum content in the sodium aluminate solution (calculated as aluminum oxide, η AO ) concentration is 150 g·L -1 , prepare 100 mL of the corresponding sodium aluminate solution, the molar ratio of aluminum ion concentration to hydroxide ion in the solution is 2:7, after the solution is prepared, put it into a constant temperature water bath at 25°C for standby use;
[0040] (2) Prepare a lithium chloride solution and add an appropriate amount of titanium tetrachloride. The titanium ion concentration in the mixed titanium-containing lithium chloride solution is 0.1 mol·L -1 ;
[0041] (3) using a constant flow pump to drop the sodium aluminate solution into the titanium-containing lithium chloride solution to cause a coprecipitation reaction, the dropping time is 30 minutes, the reaction temperature is 25° C., and an aqueous suspension is formed; the molar ratio of lithium ions in the aqueous suspension to aluminum ions in the sodium aluminate solution is 1:2, and the molar ratio of titanium to aluminum is 1:3; the microscopic morphology of the aqueous suspension in step (3) during the preparation process is as shown in FIG. Figure 4 As shown, it is demonstrated that aluminum-lithium LDH with good layer separation effect is generated.
[0042] (4) preparing a low eutectic solvent using choline chloride and urea, wherein the molar ratio of choline chloride to urea is 1:1; the volume ratio of the low eutectic solvent to the aqueous suspension in step (3) is 1:1, and adding the low eutectic solvent to the aqueous suspension prepared in step (3), heating to 90° C. for 36 hours to form a highly dispersed aluminum-lithium LDH precursor mixed solution;
[0043] (5) preparing a mixed solution of 20 g of PVC and DMF, wherein the mass ratio of PVC to DMF is 1:10, and adding the mixed solution dropwise to the highly dispersed aluminum-lithium LDH precursor mixed solution prepared in step (4) to prepare an organic phase suspension;
[0044] (6) dropping the organic phase suspension into an alcohol-containing aqueous solution to form a mixed co-precipitation to prepare a spherical porous aluminum-lithium LDH material, wherein the alcohol-containing aqueous solution used includes ethanol with a volume fraction of 50%.
[0045] The spherical porous aluminum-lithium LDH obtained by the preparation method is expressed as TiO2@PVC@AlLi-LDH, which includes porous PVC and TiO2@AlLi-LDH, wherein PVC is a porous structure, which serves as a carrier of TiO2@AlLi-LDH, and titanium oxide-doped aluminum-lithium LDH layers are dispersedly loaded on PVC.
[0046] The infrared spectra of the prepared TiO2@PVC@AlLi-LDH porous material before and after the adsorption of lithium ions were compared with the infrared spectrum of porous PVC, where the infrared spectrum of PVC is represented by PVC@Pore. Figure 3 As shown. Figure 3 It can be seen that before the adsorption of lithium ions, the infrared spectrum of PVC@Pore is basically consistent with the characteristic peak position of TiO2@PVC@AlLi-LDH. The change of some characteristic peaks is speculated to be due to the addition of aluminum-based LDH powder, and the fingerprint area of 613 and 690 cm -1 The peaks near 1500 to 1700 cm-1 disappear, indicating that there is an interaction between PVC and aluminum-lithium LDH or TiO2. -1 The characteristic peaks in the range change significantly, indicating the successful loading of Al-Li LDH on the porous material.
[0047] The porous aluminum-lithium LDH prepared in this example was tested by transmission electron microscopy before adsorption. The results are as follows: Figure 6 As shown, TiO2@PVC@AlLi-LDH was scanned before and after adsorption. The scanning electron microscope images are shown in Figure 5 As shown, (a) and (b) are scanning electron microscope images before adsorption; (c) and (d) are scanning electron microscope images after adsorption. Figure 5 , Figure 6 It can be seen that the porous materials of Al-Li LDH and the lamellar layered structures of LDH on PVC fibers were successfully synthesized.
[0048] The specific surface area of the porous aluminum-lithium LDH prepared in this example is 205.58 m 2 / g, and its adsorption capacity was tested: the adsorption was carried out on lithium hydroxide solution, the adsorption temperature was 25°C, and the adsorption time was 1h; the adsorption capacity of five cycle tests was between 19 and 21 mg·g -1 The average adsorption capacity is 20 mg g -1 .
[0049] Comparative Example 1
[0050] The difference between this comparative example and Example 1 is that no deep eutectic solvent is added in step 4), and the other operations are basically the same.
[0051] The specific surface area of the aluminum-lithium LDH prepared in this comparative example is 175.66 m 2 / g, and its adsorption capacity was tested: the adsorption was carried out on lithium hydroxide solution, the adsorption temperature was 25°C, and the adsorption time was 1h; the adsorption capacity of five cycle tests was 18-19 mg·g -1 The average adsorption capacity is 18.6 mg g -1 .
[0052] Comparative Example 2
[0053] The difference between this comparative example and Example 1 is that step (4), step (5) and step (6) are omitted, and the aqueous suspension prepared in step (3) is crystallized at a crystallization temperature of 70°C. After the reaction is completed, the adsorption material is obtained by vacuum filtration, boiling water washing, and drying at 60°C.
[0054] The specific surface area of the aluminum-lithium LDH prepared in this comparative example is 168.68 m 2 / g, and its adsorption capacity was tested: adsorption on lithium hydroxide solution, the adsorption temperature was 25℃, and the adsorption time was 1h; the adsorption capacity of five cycle tests was between 9 and 10 mg·g -1 The average adsorption capacity is 9.2 mg g -1 .
[0055] The aluminum-lithium LDH prepared in the comparative example is represented as TiO2@AlLi-LDH. The prepared aluminum-lithium LDH is tested by XRD spectra before and after adsorption. The results are as follows: Figure 2 As shown, Figure 2 (a) is the XRD spectrum before aluminum-lithium LDH adsorption. Figure 2 (b) is the XRD spectrum of porous aluminum-lithium after LDH adsorption.
[0056] The TiO2@PVC@AlLi-LDH prepared in Example 1 was tested by XRD spectra before and after adsorption. Figure 2 As shown, Figure 2 (a) is the XRD spectrum of porous aluminum-lithium before LDH adsorption. Figure 2(b) is the XRD spectrum of porous aluminum-lithium after LDH adsorption.
[0057] Comparing the XRD patterns of TiO2@PVC@AlLi-LDH prepared in Example 1 with those of TiO2@AlLi-LDH prepared in this comparative example, it can be seen that the crystallization of titanium oxide-doped lithium aluminum LDH (TiO2@AlLi-LDH) prepared directly from the aqueous suspension prepared by mixing titanium-containing lithium chloride solution and sodium aluminate solution is poor. After the porous material is prepared in combination with PVC, the layer of lithium aluminum LDH (TiO2@PVC@AlLi-LDH) is highly dispersed, resulting in further broadening of the characteristic peaks of the crystal, especially the broadening of the characteristic peaks at 20.62° and 23.68°, and the absence of characteristic peaks at 63.22° and 64.53°, and the diffraction peaks merge into a broad peak state.
[0058] Comparative Example 3
[0059] The difference between this comparative example and Example 1 is that in step (6), the highly dispersed aluminum-lithium LDH precursor mixture is dripped into deionized water, and the rest of the operations are basically the same. The specific surface area of the adsorption amount of the porous aluminum-lithium LDH prepared in this comparative example is 165.56 m 2 / g, and its adsorption capacity was tested: the adsorption was carried out on lithium hydroxide solution, the adsorption temperature was 25°C, and the adsorption time was 1h; the adsorption capacity of five cycle tests was 16-18mg·g -1 The average adsorption capacity is 17.6 mg g -1 .
[0060] Example 2
[0061] (1) Aluminum hydroxide and sodium hydroxide are used as raw materials to prepare a sodium aluminate solution. The aluminum content in the sodium aluminate solution (calculated as aluminum oxide, η AO ) concentration is 80 g·L -1 , prepare 100 mL of the corresponding sodium aluminate solution, the molar ratio of aluminum ion concentration to hydroxide ion in the solution is 2:8, after the solution is prepared, put it into a constant temperature water bath at 25°C for standby use;
[0062] (2) Prepare a lithium chloride solution and add an appropriate amount of titanium tetrachloride; the titanium ion concentration in the titanium-containing lithium chloride solution after mixing is 0.15 mol·L -1 ;
[0063] (3) using a constant flow pump to dropwise add the sodium aluminate solution into the titanium-containing lithium chloride solution to cause a coprecipitation reaction, the dropping time is 30 minutes, the reaction temperature is 50° C., and an aqueous suspension is formed, wherein the molar ratio of lithium ions in the aqueous suspension to aluminum ions in the sodium aluminate solution is 1.5:2, and the molar ratio of titanium to aluminum is 1:4;
[0064] (4) preparing a low eutectic solvent using DBU and MTU, wherein the molar ratio of DBU to MTU is 1:1, the volume ratio of the low eutectic solvent to the aqueous suspension in step (3) is 1:1, and adding the low eutectic solvent to the aqueous suspension prepared in step (3), heating to 80° C. for 48 hours to form a highly dispersed aluminum-lithium LDH precursor mixed solution;
[0065] (5) preparing a mixed solution of 20 g of PVC and DMF, wherein the mass ratio of PVC to DMF is 1:8, and adding the mixed solution dropwise into the highly dispersed aluminum-lithium LDH precursor mixed solution prepared in (4) to prepare an organic phase suspension;
[0066] (6) dropping the organic phase suspension into an alcohol-containing aqueous solution to form a mixed co-precipitation to prepare a spherical porous aluminum-lithium LDH material, wherein the alcohol-containing aqueous solution used includes ethanol with a volume fraction of 30%.
[0067] The specific surface area of the porous aluminum-lithium LDH prepared in this example is 198.57 m 2 / g, and its adsorption capacity was tested: the adsorption was carried out on lithium hydroxide solution, the adsorption temperature was 25°C, and the adsorption time was 1h; the adsorption capacity of five cycle tests was 19-22mg·g -1 The average adsorption capacity is 19.58 mg g -1 .
[0068] Example 3
[0069] (1) Aluminum hydroxide and sodium hydroxide are used as raw materials to prepare a sodium aluminate solution. The aluminum content in the sodium aluminate solution (calculated as aluminum oxide, η AO ) concentration is 120 g·L -1 , prepare 100 mL of the corresponding sodium aluminate solution, the molar ratio of aluminum ion concentration to hydroxide ion in the solution is 2:10, after the solution is prepared, put it into a constant temperature water bath at 25°C for standby use;
[0070] (2) Prepare a lithium chloride solution and add an appropriate amount of titanium tetrachloride; the titanium ion concentration in the titanium-containing lithium chloride solution after mixing is 0.2 mol·L -1 ;
[0071] (3) using a constant flow pump to dropwise add the sodium aluminate solution into the titanium-containing lithium chloride solution to cause a coprecipitation reaction, the dropping time is 30 minutes, the reaction temperature is 60° C., and an aqueous suspension is formed; the molar ratio of lithium ions in the aqueous suspension to aluminum ions in the sodium aluminate solution is 2:2, and the molar ratio of titanium to aluminum is 1:5;
[0072] (4) preparing a low eutectic solvent using DBU and MTU, wherein the molar ratio of DBU to MTU is 1:1, and the volume ratio of the low eutectic solvent to the aqueous suspension in step (3) is 1:1, and adding the low eutectic solvent to the aqueous suspension prepared in step (3), heating to 120° C. for 24 hours to form a highly dispersed aluminum-lithium LDH precursor mixed solution;
[0073] (5) preparing 20 g of a mixed solution of PVC and DMF, wherein the mass ratio of PVC to DMF is 1:12, and adding the mixed solution dropwise into the mixed solution of the highly dispersed aluminum-lithium LDH precursor prepared in (4) to prepare an organic phase suspension;
[0074] (6) The organic phase suspension is dropped into an alcohol-containing aqueous solution to form a mixed coprecipitation to prepare a spherical porous material. Methanol with a volume fraction of 10% can be added to the aqueous phase.
[0075] The specific surface area of the porous aluminum-lithium LDH prepared in this example is 201.22 m 2 / g, and its adsorption capacity was tested: the adsorption was carried out on lithium hydroxide solution, the adsorption temperature was 25°C, and the adsorption time was 1h; the adsorption capacity of the five cycle tests was 19-22mg·g -1 The average adsorption capacity reached 21.58 mg·g -1 .
Claims
1. A porous aluminum lithium LDH for lithium ion adsorption, characterized in that: It includes porous PVC and titanium oxide doped aluminum lithium LDH, wherein the porous PVC is used as a carrier, and the titanium oxide doped aluminum lithium LDH layer is dispersedly loaded on the PVC; The LDH characteristic peaks at 20.62°, 23.68°, 63.22° and 64.53° in its XRD pattern are significantly broadened compared with those of TiO2@AlLi-LDH.
2. The porous aluminum lithium LDH for lithium ion adsorption according to claim 1, characterized in that: The specific surface area of the porous aluminum-lithium LDH is 198.57-205.58 m 2 / g; and / or the adsorption capacity of the porous aluminum lithium LDH is 19 to 22 mg·g -1 .
3. A method for preparing porous aluminum lithium LDH for lithium ion adsorption, characterized in that: include: The aluminum ions, lithium ions and titanium ions are contacted or mixed in an alkaline aqueous solution to cause a coprecipitation reaction to form an aqueous suspension; Adding a low eutectic solvent to the aqueous suspension and evaporating the solvent to remove water, so as to form a highly dispersed aluminum-lithium LDH precursor mixed solution; Adding a mixed solution of PVC and DMF to the aluminum-lithium LDH precursor mixed solution to form an organic phase suspension; The organic phase suspension is dripped into the aqueous phase to prepare the porous aluminum-lithium LDH.
4. The method for preparing porous aluminum lithium LDH for lithium ion adsorption according to claim 3, characterized in that: The deep eutectic solvent is a combination of choline chloride and urea, or a combination of DBU and MTU, or a combination of other deep eutectic solvents containing a hydroxyl structure.
5. The method for preparing porous aluminum lithium LDH for lithium ion adsorption according to claim 3, characterized in that: The evaporation of the aqueous suspension to remove water is specifically carried out by heating the aqueous suspension to a temperature of 80 to 120° C. for a duration of 24 to 48 hours.
6. The method for preparing porous aluminum lithium LDH for lithium ion adsorption according to claim 3, characterized in that: The mass ratio of PVC to DMF is 1:(8-12), and the mixed solution thereof is added dropwise into the mixed solution of highly dispersed aluminum lithium LDH precursor.
7. The method for preparing the porous aluminum lithium LDH for lithium ion adsorption according to any one of claims 3 to 6, characterized in that: The contacting or mixing of aluminum ions, lithium ions and titanium ions in an alkaline aqueous solution specifically includes: adding titanium tetrachloride to the lithium salt solution to obtain a lithium salt solution containing titanium; And / or mixing the sodium aluminate solution with a titanium-containing lithium salt solution.
8. The method for preparing porous aluminum lithium LDH for lithium ion adsorption according to claim 7, characterized in that: The concentration of aluminum ions in the sodium aluminate solution is 80-150 g / L, wherein the ratio of the molar number of aluminum ions to the molar number of hydroxide ions is 2:(7-10).
9. The method for preparing porous aluminum lithium LDH for lithium ion adsorption according to claim 7, characterized in that: The sodium aluminate solution is mixed with the titanium-containing lithium salt solution, specifically, the sodium aluminate solution is added dropwise to the titanium-containing lithium chloride solution using a constant flow pump, and the mixing temperature is 25-60° C.; the molar ratio of lithium to aluminum in the aqueous suspension is (1-2):2, and the molar ratio of titanium to aluminum is 1:(3-5).
10. The method for preparing porous aluminum lithium LDH for lithium ion adsorption according to claim 9, characterized in that: The aqueous phase is an alcohol-containing aqueous solution, and the alcohol-containing aqueous solution includes ethanol or methanol with a volume fraction of 10 to 50%.
Citation Information
Patent Citations
Magnetic microporous lithium adsorption agent and preparation method and application thereof
CN109078602A
Preparation method of magnetic aluminum salt lithium adsorbent
CN110639467A